Attainable regions and fuzzy multi-criteria decisions: Modeling a novel configuration of methane bioreactor using experimental limits of operation. (January 2020) - Abunde Neba, F.; Asiedu, Nana Y.; Addo, Ahmad; Seidu, Razak
Highlights: Optimal digester structures can be synthesized even without a kinetic model. Anaerobic treatability study is conducted using abattoir effluent. The approach uses an attainable region technique to model digester structures. A novel attainable-region-inspired digester prototype is developed. Optimal batch operation involves 2 batch with intermittent semi-batch digesters. Abstract: This study sets out to develop an approach that couples attainable regions and fuzzy multicriteria decision methods for modeling optimal configurations of multistage digesters without using a kinetic model of the process. The approach is based on geometric analysis of methane curves as their shapes contain valuable insight into substrate biodegradability characteristics during anaerobic digestion. With the case study of abattoir waste, the results indicate that the optimal batch operation policy involves four anaerobic sequencing batch reactors operated in series with fresh feed being added at the second and the four stages (fed-batch systems). For continuous mode operation, the optimal configuration involves a continuous stirred tank digester with bypass from feed followed by an anaerobic baffled digester, which has been used to obtain a novel prototype. The methodological framework presented in this study can be adopted to enhance design of multistage anaerobic digesters especially when reliable kinetic models are unavailable.